A prediction model for determining the fracture toughness of saturated asphalt concrete in sub-zero temperatures - Fakhri, Mansour; Siyadati, Sayyed Ali; Aliha, M.R.M (Theoretical and applied fracture mechanics, 2025)
Cracks in asphalt concrete due to decreasing temperatures are common in cold regions. As the number of temperature cycles increases, crack growth accelerates. After precipitation, water enters the asphalt’s air voids, and in sub-zero temperatures, the formation of ice crystals causes further damage, leading to an increased risk of surface cracking. In this research, the influence of freeze–thaw cycles (FTCs) on the fracture toughness (FT) of saturated asphalt specimens has been assessed utilizing the fracture mechanics method in pure and mixed modes; furthermore, a prediction model has been presented. The asphalt specimens were prepared in the form of Semi-Circular Bend (SCB). After saturating the SCB samples, they were subjected to a maximum of 11 FTCs. Then, the specimens were fractured at three sub-zero temperatures including −8 °C, −18 °C and –22 °C, using a three-point bend loading setup in four fracture modes (Me = 0,0.38, 0.8 and 1). The selected temperatures were determined based on meteorological data obtained from city of Qazvin in Qazvin Province, Iran, and the K-means clustering method to closely simulate the actual temperature conditions experienced by pavements. The outcomes of this research illustrate that as the number of FTCs increases, the FT decreases. Also, after cycle number seven, the reduction in the rate of FT reduction significantly slowed. Reducing the temperature to −18 °C gives rise to an increase in the resistance of the specimens against fracture; however, a further decrease in temperature results in a decrease in the resistance of samples against failure. The minimum resistance of specimens occurred in 0.4 < Me < 0.8, and in pure modes, higher resistance was observed. The FTC cycles used in this research will provide more realistic results than the cycles suggested by AASHTO T-283 standard. Eventually, among the variables, including FTCs, temperature, and loading modes, FTCs has the most significant impact on FT.